La interpretación en el derecho tributario - Chávez Gonzales, Ángel Marco (2021)
Tax controversies in part are originated by the different interpretations of the tax regulations between tax administration and taxpayers, so the issue of the interpretation of the tax regulations is of academic interest for this reason we have resorted to the doctrine and from a practical point of view to the resolutions of the Tax Court and the judgments of the Supreme Court. This article begins showing what tax controversies mean in numbers; then referring to the a priori approach of the interpreter, known as general interpretation criteria; also we will discuss the methods of interpretation; after we will see the apothegms of interpretation, which are topical arguments of fairly general acceptance; finalizing the article with the analogy, the excessive interpretation of the rule and the interpretation of the tax relief.